2016
DOI: 10.1016/j.mjafi.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis: Indian scenario

Abstract: Viral hepatitis is a cause for major health care burden in India and is now equated as a threat comparable to the "big three" communicable diseases - HIV/AIDS, malaria and tuberculosis. Hepatitis A virus and Hepatitis E virus are predominantly enterically transmitted pathogens and are responsible to cause both sporadic infections and epidemics of acute viral hepatitis. Hepatitis B virus and Hepatitis C virus are predominantly spread via parenteral route and are notorious to cause chronic hepatitis which can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 48 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…In India, sporadic hepatitis A virus (HAV) and hepatitis E virus (HEV) infections as well as waterborne outbreaks are frequent. 1,2 Hepatitis A virus exposure typically occurs early in life, when the infection is often subclinical. Serological studies in India in recent decades indicate a consistent pattern of high HAV exposure during childhood, with more than 80% of children demonstrating antibodies against the virus by age 10 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In India, sporadic hepatitis A virus (HAV) and hepatitis E virus (HEV) infections as well as waterborne outbreaks are frequent. 1,2 Hepatitis A virus exposure typically occurs early in life, when the infection is often subclinical. Serological studies in India in recent decades indicate a consistent pattern of high HAV exposure during childhood, with more than 80% of children demonstrating antibodies against the virus by age 10 years.…”
mentioning
confidence: 99%
“…The overall disease rates are generally low, and outbreaks are rare because of the high level of population immunity. [1][2][3] The seroprevalence data in India also indicate higher prevalence of HAV among children, although a few pockets of low seroprevalence have been reported in urban areas with higher levels of socioeconomic development. 2 The data from VRDLs showed that HAV accounted for 13.9% of the viral hepatitis cases tested by these laboratories and nearly three-fourths of these patients were aged < 19 years.…”
mentioning
confidence: 99%
“…It can take several months to a year to regain good health. 1 Hepatitis B virus is a DNA virus belongs to Hepadnaviridae family. 2 It is a leading cause of chronic hepatitis, cirrhosis, and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving chronic haemodialysis (CHD) treatment are dialyzed three times per week with each dialysis session lasting up to four hours [ 7 ] during which excess body fluid and toxic components such as urea are removed out of the body [ 6 ]. On the other hand, peritoneal dialysis especially Continuous Ambulatory Peritoneal Dialysis (CAPD) has received varied acceptance among African countries due to high costs of peritoneal fluids [ 8 , 9 ]. Furthermore, high rates of infection among patients using peritoneal dialysis raises a concern for those in Africa where most of the people still reside in unhygienic environments which lack clean water, low electric supply and limited sanitary education [ 10 ].…”
Section: Introductionmentioning
confidence: 99%